PENGEMBANGAN BUKU SAKU DIGITAL BERBASIS MASALAH UNTUK MEMFASILITASI KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Melinda, Tasya Safa; Sutrisno AB, Joko; Kirana, Arinta Rara (LP4MK STKIP PGRI Lubuklinggau, 2023)
This research aims to analyze the feasibility of a problem-based digital pocketbook on the System of Two Variable Linear Equations (SPLDV) material developed in terms of its validity, attractiveness, practicality and effectiveness of use in facilitating mathematical problem-solving abilities. Product development using the ADDIE model was carried out in class VIII of SMP Negeri 7 Tulang Bawang Barat. Questionnaire and test techniques were used for data collection. The validation results for material experts obtained a score of 4.53, media experts 4.50 and language experts 4.36, which shows valid criteria. The average student response was 4.55 or interesting, and the teacher response was 4.83 or practical. From the evaluation results of students' mathematical problem-solving abilities after implementation, it is known that classical learning completeness reached 91% or very high. It can be concluded that problem-based digital pocketbooks are suitable for use as learning media to facilitate mathematical problem-solving abilities.